Tissue-Specific Dynamics in the Endophytic Bacterial Communities in Arctic Pioneer Plant Oxyria digyna - Given, Cindy; Häikiö, Elina; Kumar, Manoj; Nissinen, Riitta (Frontiers in Plant Science, 2020)
The rapid development in the next-generation sequencing methods in the recent years have provided more information regarding the community structures and functions of endophytic bacteria. However, the assembly rules of these communities in different plant tissues are currently poorly understood. The aim of this study was to investigate if the taxonomic composition of endophytic bacterial communities in leaf and root are different and whether plant tissue (leaves or roots) or plant origin (bait or wild plants) affect the assembly of the endophytic bacterial communities. To address this, we planted micropropagated Oxyria digyna plants with low bacterial load (bait plants) in experimental site with native O. digyna population in Low Arctic. The endophytic community structures in the leaves and roots of the bait plants was analyzed after one growing season and one year in the field, and compared them to those of the wild plants growing at the same site. 16S rRNA gene targeted sequencing revealed that endophytic communities in the roots were more diverse than in the leaves, and the diversity in the bait plants increased in the field, and was highest in the wild plants. Both tissue type and plant group had strong impact on the endophytic bacterial community structures. Firmicutes were highly abundant in the leaf communities of both plant types, while Proteobacteria were more abundant in the roots. The community structures in the bait plants changed in the field over time, and increasingly resembled the wild plant endophytic communities. This was due to the changes in the relative abundances of several bacterial taxa, as well as species acquisition in the field. Several OTUs that were acquired by the bait plants in the field and were shared with the wild plants represent putative diazotrophic taxa, suggesting major role for nitrogen fixation in the nutrient poor arctic soils.